Parental burnout, depression and emotional development of the preschoolers - Yakupova, Vera; Suarez, Anna (Frontiers in Psychology, 2023)
Parental burnout is becoming more and more prevalent in the world, mainly in cultures with high demands towards parents. Parental burnout is distinctive from depression and might have its unique influence on child development, which is under current international research. This work contributes to the understanding of parental burnout, maternal depression and child emotional development (specifically emotion comprehension) interrelations. Additionally, we explored whether there are differences in the effects of parental burnoutPB and depression on boys and girls. The regression analysisdata obtained shows that parental burnout positively correlates with child emotional comprehension skills, specifically understanding of external causes (B= 0.20, CI: 0.03; 0.37) and mental causes of emotions (B = 0.22, CI: 0.05; 0.40). This effect is gender dependent and is significantly higher for girls (B= 0.54, CI: 0.09; 0.98). The effect of maternal depression on emotion comprehension skills is also gender dependent: total scores on emotion comprehension tasks are significantly higher for daughters of mothers with depression (B= 0.59, CI: 0.001; 1.18).